Single-crystal-to-single-crystal transformation in hydrogen-bond-induced high-spin pseudopolymorphs from protonated cation salts with a π-extended spin crossover Fe(III) complex anion. (4th November 2017) - Murata, Suguru; Takahashi, Kazuyuki; Sakurai, Takahiro; Ohta, Hitoshi
Graphical abstract: The crystal structures and magnetic properties of novel protonated dabco CH2 Cl2 -solvate compound1 and hydrate compound2 with a π-extended spin crossover Fe(III) anion revealed that hydrogen-bonding interactions induced the coordination structure distortion affording the high-spin Fe(III) anion and participated in intermolecular interaction frameworks which can support a single-crystal-to-single-crystal transformation of1 into2 . Abstract: Novel pseudopolymorphic Hdabco compounds with an Fe(III) complex anion, (Hdabco)[Fe(aznp)2 ]·CH2 Cl2 1 and (Hdabco)[Fe(aznp)2 ]·0.5H2 O2 [dabco = 1, 4-diazabicyclo[2.2.2]octane, H2 aznp = (2′-hydroxyphenylazo)-2-hydroxynaphthalene], were prepared and characterized. The magnetic susceptibility for1 and2 revealed that both complexes were in a high-spin (HS) state in the whole temperature range and exhibited weak ferromagnetic interactions below 40 K. The crystal structural analyses suggested that strong N–H⋯O hydrogen bonding interactions between the Hdabco cation and [Fe(aznp)2 ] anion may induce the distortion of a coordination structure resulting in the HS complexes, whereas π-stacking interactions between the π-ligands in the [Fe(aznp)2 ] anion and additional C–H⋯N hydrogen bonding interactions between the Hdabco cation and [Fe(aznp)2 ] anion constructed a intermolecular interaction framework structure with one-dimensional channels. The thermogravimetry analysis for compound1 indicated the adsorption of a water molecule took place after the desorption of a dichloromethane molecule. This transformation of1 into2 proved to proceed in a single-crystal-to-single-crystal way by powder X-ray diffractions and single crystal X-ray structural analysis.